Specialized metabolites of the United States lichen Niebla homalea and their antiproliferative activities. (December 2020) - Zhang, Yan; Tan, Choon Yong; Spjut, Richard W.; Fuchs, James R.; Kinghorn, A. Douglas; Rakotondraibe, Liva Harinantenaina
Abstract: Three undescribed stictanes, nieblastictanes A−C, two flavicanes, nieblaflavicanes A and B, together with three already reported stictanes, along with the known compounds (+)-usnic acid, sekikaic acid, divaricatic acid, and divaricatinic acid methyl ester were isolated from an ethyl acetate extract of the western North American lichen Niebla homalea . The structures of the new and known compounds were established by spectroscopic methods including nuclear magnetic resonance spectroscopy, mass spectrometry and electronic circular dichroism. Among the compounds isolated, usnic acid exhibited moderately potent antiproliferative activities against the A2780 ovarian (IC50 3.8 μM) and MCF-7 breast cancer (IC50 6.8 μM) cell lines. A plausible mode of formation of the chlorine-containing compound nieblastictane C is provided and the contribution of the isolated compounds to the chemotaxonomy of United States lichen species of the genus Niebla is also discussed. Graphical abstract: Image 1 Highlights: Extract of Niebla homalea yielded undescribed triterpenes and aromatic compounds of chemotaxonomic interests. The present Niebla homalea sample belongs to the triterpenes and depsides clade. Usnic acid was the most active compound against the proliferation of ovarian and breast cancer cell lines.